2017
DOI: 10.3324/haematol.2016.156281
|View full text |Cite
|
Sign up to set email alerts
|

c-Myc dysregulation is a co-transforming event for nuclear factor-κB activated B cells

Abstract: While c-Myc dysregulation is constantly associated with highly proliferating B-cell tumors, nuclear factor (NF)-κB addiction is found in indolent lymphomas as well as diffuse large B-cell lymphomas, either with an activated B-cell like phenotype or associated with the Epstein-Barr virus. We raised the question of the effect of c-Myc in B cells with NF-κB activated by three different inducers: Epstein-Barr virus-latency III program, TLR9 and CD40. Induction of c-Myc overexpression increased proliferation of Eps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…Transcriptome results suggested that PD-L1 expression during EBV latency III/proliferation program was mainly due to LMP1, the main EBV oncogene (unpublished data and ( [20]). To confirm this result, the EREB2-5 cell line, an EBV latency III cell line that is estradiol conditional for EBNA2 activity (essential for the initiation of the latency III program expression) (21) was stably transfected with the doxycycline-regulatable PRT1 vector in which the cassette was a cDNA coding for either Luc, LMP1-Wt, or a dominant negative variant of LMP1, LMP1-CT (22).…”
Section: Ebv Latency Iii-transformed B Cells Express Pd-l1 In An Lmp1mentioning
confidence: 93%
“…Transcriptome results suggested that PD-L1 expression during EBV latency III/proliferation program was mainly due to LMP1, the main EBV oncogene (unpublished data and ( [20]). To confirm this result, the EREB2-5 cell line, an EBV latency III cell line that is estradiol conditional for EBNA2 activity (essential for the initiation of the latency III program expression) (21) was stably transfected with the doxycycline-regulatable PRT1 vector in which the cassette was a cDNA coding for either Luc, LMP1-Wt, or a dominant negative variant of LMP1, LMP1-CT (22).…”
Section: Ebv Latency Iii-transformed B Cells Express Pd-l1 In An Lmp1mentioning
confidence: 93%
“…Our previous transcriptome studies from L.CD40 mice suggested that those tumors might express high levels of CD274/PD-L1 (6). We thus analyzed the Immune Escape Gene Signature published by C Laurent et al (Supplemental Table 1) (7) from the Affymetrix transcriptome (HT MG-430 PM Array, Supplemental Tables 2 and 3) of a series of six L.CD40 B-cell lymphomas that were compared to their CD19_Cre littermate.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of TA application, p38 MAPK can also be involved. In addition, the TA can activate the classical signal cascade of TLR, activation ends by the expression induction of many genes, including с-Myc, via NF-kB transcriptional factor (50). Furthermore, MAPK induces the transcription of early c-Fos and c-Myc genes, which produce transcription factors and provide the transcription of late genes responsible for proliferation, survival, and cell motility (23).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MAPK induces the transcription of early c-Fos and c-Myc genes, which produce transcription factors and provide the transcription of late genes responsible for proliferation, survival, and cell motility (23). In addition, the TA can activate the classical signal cascade of TLR, activation ends by the expression induction of many genes, including с-Myc, via NF-kB transcriptional factor (50). As a matter of fact, a high expression of c-Myc is usually observed during active cell growth and proliferation (51).…”
Section: Discussionmentioning
confidence: 99%